1996
DOI: 10.1080/03601239609373047
|View full text |Cite
|
Sign up to set email alerts
|

Colloid-facilitated transport of metolachlor through intact soil columns

Abstract: This study evaluated the role of water dispersible colloids with diverse physicochemical and mineralogical characteristics in facilitating the transport of metolachlor through macropores of intact soil columns. The soil columns represented upper solum horizons of an Alfisol in the Bluegrass region of Kentucky. Three different colloid suspensions tagged with metolachlor [2-chloro-N-(2-ethyl-6-methylphenyl)-N-(2-methoxy-l-methylethyl)acetamide] were introduced at a constant flux into undisturbed soil columns. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…It has been suggested that preferential flow may contribute significantly to the movement of pesticides in soil,7, 11, 15 although the transport mechanisms are not known in detail. A number of studies have dealt with the issue of colloid‐facilitated transport 16. 17 Structural heterogeneity, in particular the presence of continuous macropores, may enhance the mobility of particles and sorbed contaminants because adsorption, sedimentation and sieving are less pronounced in large pores 18.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that preferential flow may contribute significantly to the movement of pesticides in soil,7, 11, 15 although the transport mechanisms are not known in detail. A number of studies have dealt with the issue of colloid‐facilitated transport 16. 17 Structural heterogeneity, in particular the presence of continuous macropores, may enhance the mobility of particles and sorbed contaminants because adsorption, sedimentation and sieving are less pronounced in large pores 18.…”
Section: Introductionmentioning
confidence: 99%
“…4.12) (Seta and Karathanasis, 1996). This is the result of the higher adsorption coefficient (3-to 5-fold) of metolachlor over that of atrazine for soil and colloid surfaces.…”
Section: Herbicidesmentioning
confidence: 91%
“…As per the above discussion, Ives (1975) concluded that sedimentation was likely to be unimportant due to the small diameter of colloidal particles. Some studies have investigated the passing of colloidal materials through soil columns (Awedat, 2014;Lahav, 1980;Seta and Karathanasis, 1996) with the major findings being that greater macroporosity causes greater colloidal transport and that there is usually a higher concentration of attached colloids nearer the surface layers. Of importance, a study by Toran and Palumbo (1992) sought to determine how influential chemical effects were on colloidal attachment via infiltration of artificially fractured columns.…”
Section: Treatmentmentioning
confidence: 99%